Association of SNPs in GnRH gene with sperm quality traits of Chinese water buffalo. Issue 3 (28th January 2020) - Wang, Siyao; Zhang, Yining; Cheng, Yunyun; Lu, Guanhong; Yang, Rui; Geng, Hongwei; Wang, Chunli; Li, Haoyang; Feng, Tianqi; Liu, Songcai; Hao, Linlin
Abstract: Hypothalamic gonadotropin‐releasing hormone (GnRH) controls the activity of hypothalamic–pituitary–gonadal axis and plays a key role in the reproductive performance of animals. In this study, five single nucleotide polymorphisms (SNPs), namely g.991T > C, g.1041T > C g.3424T > C, g.3462C > A and g.3463Inde A, were detected in the GnRH gene of 162 water buffaloes by Sanger sequencing. Each SNP was associated with more than two sperm quality traits of ejaculate volume, sperm concentration, post‐thaw sperm motility and sperm abnormality. g.3424T > C and g.3462C > A were related to these four traits and had a remarkable effect on ejaculate volume. The three other SNPs were related to sperm concentration, post‐thaw sperm motility and sperm abnormality. Moreover, six haplotypes (H1: TCCAI, H2: CTTC‐, H3: TCCCI, H4: CTTA‐, H5: CCTA‐ and H6: CTCC‐) composed of five SNPs comprising seven different combined genotypes were generated by linkage disequilibrium analysis. Statistics followed by one‐way ANOVA indicated that water buffaloes with the haplotype combination H1H1 had the highest genotypic frequency, and those with the H4H4 haplotype combination had the highest ejaculate volume. The sperm concentration of those with haplotype combination H1H5 was higher than that of the other genotypes. In summary, our study showed a remarkable association between the SNPs of GnRH and sperm quality traits of Chinese water buffalo.